Preventive percutaneous coronary intervention and aspiration thrombectomy—updates in the management of ST-elevation myocardial infarction - Wald, David S.; Bestwick, Jonathan P. (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
The management of patients with acute ST-elevation myocardial infarction (STEMI) has undergone change in recent years with associated reductions in mortality (1). The short-term goal of treatment is to restore blood flow to the occluded infarct artery. Prompt percutaneous coronary intervention (PCI) and stenting of the stenosis causing the occlusion reduces the risk of cardiac death and recurrent infarction (2). Recently, the American College of Cardiology and American Heart Association (ACC/AHA) recommended preventive PCI and to stop using aspiration thrombectomy (3).